Predictors of quality of life in older adults benefitting from institutionalized care and support during the COVID-19 pandemic - Bobrowicz-Campos, E.; Justo-Henriques, S. (3º Congresso Internacional AGE.COMM, 2023)
This observational study with mixed-method design aimed to identify the main predictors of quality of life in older adults who benefited from institutionalized care and support during the COVID-19 pandemic. The study was registered in ClinicalTrials.gov (NCT05379426) and was approved by the Ethics Committee from the Health Science Research Unit: (Approval Number: P871_04_2022). Fifty-eight institutions (nursing homes, adult day centres, and home support services located in different regions of Portugal) got involved in the study, recruiting a total of 878 potential participants. Of these, 847 met the eligibility criteria, and 845 completed the assessment procedures. Data were collected between June and July 2022, using sociodemographic and clinical questionnaires, as well as the Quality of Life in Alzheimer's Disease scale, Centre for Epidemiologic Studies Depression Scale, Geriatric Anxiety Inventory, Loneliness Scale, Mini-Mental State Examination and Frontal Assessment Battery. Additionally, a semi-structured interview was conducted on the difficulties experienced during the pandemic period. To establish which variables better explain quality of life (overall and in the social, psychological, and physical domains), multivariate regression analyses, using a stepwise method, were performed. These analyses were undertaken separately for older adults residing in nursing homes (n = 612) and for older adults residing in the community (n = 233). Depression, loneliness, cognitive functioning, age, and informal support network were the significant predictors of quality of life in both older adults’ groups. In residents of nursing homes, additional influence of anxiety and education was established. As for the older adults from the community, additional contribution of health status was verified. The study findings will be discussed considering the testimonies obtained through the interviews, which will contribute to a better understanding of the experiences of the older adults during the pandemic period, and which will allow outlining responses to minimize the negative impact of these experiences.